Comparative bio-ecological studies among two species of Urentius lace bugs (Hemiptera: Tingidae) in Sudan - Abdalla Abdelrahim Satti; El Imam El Khidir (Journal of the Saudi Society of Agricultural Sciences, 2012)
Among the prevalent lace bugs in Sudan, Urentius hystricellus and Urentius euonymus are important pests of eggplant and pigeon pea, respectively. They attack alternative hosts, but some plants were reported as common hosts for both species. In fact, the identity of these pests and their actual host plants seems to be confusing. Therefore, the main objectives of this work were to; differentiate between such pest species based on certain morpho-biological investigations, verify their hosts’ ranges and study their intra-host distributions and seasonal trends through field surveys and experiments. The results showed clear morphological and biological differences among the two lace bug species. The durations of pre-imaginal stages of U. hystricellus were shorter than those of U. euonymus, while each pest took shorter durations in autumn as compared with winter season. Each pest has its own host range, and no shared hosts were detected, as believed. Hence, the mistaken hosts were corrected and new hosts were added. Such new records included Solanum incanum for U. hystricellus, and two hosts (Chrozophora plicata and Rhynchosia memnonia) for U. euonymus. Counts of insects on either leaf sides have revealed variable distributions in different hosts. The seasonal trends of the two pests showed peak populations during autumn and summer seasons. In conclusion, the study made clear distinctions between U. hystricellus and U. euonymus, and gave supportive findings for ecological management.